Romania : Technical Assistance Report on Reforming Personal Income Taxation. (IMF Staff Country Reports; Country Report, 2022)
With one of the lowest revenues in the EU and a projected budget deficit exceeding 7 percent of GDP, Romania should rely on an array of tax (policy and administration) instruments to mobilize revenues. A fundamental question facing Romania's reform efforts is how to spread the burden of the tax in an equitable manner, especially given the already relatively high income inequality. The fiscal system as a whole currently provides little income support at the bottom of the income distribution.